Reinforced odor representations in the anterior olfactory nucleus can serve as memory traces for conspecifics: new research sensory and motor systems - Linster, Christiane; Wolf, David; Kelsch, Wolfgang (eNeuro, 2025)
Recognition of conspecific individuals in mammals is an important skill, thought to be mediated by a distributed array of neural networks, including those processing olfactory cues. Recent data from our groups have shown that social memory can be supported by olfactory cues alone and that interactions with an individual lead to increased neural representations of that individual in the anterior olfactory nucleus, an olfactory network strongly modulated by the neuropeptide oxytocin. We here show, using a computational model, how enhanced representations in the AON can easily arise during the encoding phase, how they can be modulated by OXT, and how a dynamic memory signature in the form of enhanced oscillations in the beta range arises from the architecture of the neural networks involved. These findings have implications for our understanding how social memories are formed and retrieved and generate further hypotheses that can be tested experimentally.
Online veröffentlicht: 15. Juli 2025
Gesehen am 11.09.2025